Budget Efficiency vs Public Service: A Critical Evaluation of Presidential Instruction No. 1 of 2025 - Munawir Munawir; Agus Suherman; Naufal Haidar Ahmada (Journal of Law and Economics, 2025)
This study evaluates Presidential Instruction No. 1/2025 on Budget Efficiency using William N. Dunn's policy evaluation model across five dimensions: effectiveness, efficiency, adequacy, responsiveness, and equity. The policy mandates IDR 256.1 trillion in budget cuts, including IDR 50.59 trillion in regional transfers. The qualitative-descriptive approach analyzes official policy documents, Ministry of Finance publications, Indonesia Corruption Watch data, and international literature on OECD fiscal consolidation practices. While aiming to reduce wasteful spending, the blanket-cutting approach—lacking performance-based evaluation and empirical evidence—threatens service delivery in education, health, and infrastructure. Regional transfer cuts undermine local autonomy and service capacity, particularly concerning given that 88% of regions depend on central transfers. Comparative analysis with Australia, Latvia, and Chile reveals that Presidential Instruction No. 1/2025 lacks critical mechanisms: ring-fencing protections, performance-based evaluation, results-driven incentives, and adequate compensation schemes. The study recommends temporary moratoriums for vital sectors, systematic spending review mechanisms, selective budget reduction targeting ineffective and leakage-prone programs, and strengthened institutional capacity for value-for-money budget management. Implementation requires strong political commitment, effective inter-governmental coordination, and robust information systems to achieve fiscal efficiency without sacrificing public service quality.